A role for p53 in telomere protection. (2nd November 2017) - Tutton, Stephen; Lieberman, Paul M.
ABSTRACT: Telomeres cap the ends of chromosomes and are crucial for genome stability. The p53 protein (TP53) is a vital tumor suppressor, activating the transcription of numerous genes in response to cell stress. We reported that direct binding of p53 at human subtelomeres corresponds with local transcription activation and enhanced telomere stability in the presence of DNA damage.